Design Thinking : process and methods manual - Curedale, Robert
Design Thinking is an approach to designing products, services, architecture, spaces and experiences that is being quickly adopted by designers, architects and some of the world's leading brands such as GE, Target, SAP, Procter and Gamble, IDEO and In